Metabolic Effects of the Cancer Metastasis Modulator MEMO1 - Marziyeh Ghanbarian; Natalia Dolgova; Frederick S. Vizeacoumar; Franco J. Vizeacoumar; Deborah Michel; Anas El-Aneed; Oleg Y. Dmitriev (Metabolites)
Background/Objectives: Cancer cells often display altered energy metabolism. In particular, expression levels and activity of the tricarboxylic acid cycle (TCA cycle) enzymes may change in cancer, and dysregulation of the TCA cycle is a frequent hallmark of cancer cell metabolism. MEMO1, a modulator of cancer metastasis, has been shown to bind iron and regulate iron homeostasis in the cells. MEMO1 knockout changed mitochondrial morphology and iron content in breast cancer cells. Our previous genome-wide analysis of MEMO1 genetic interactions across multiple cancer cell lines revealed that gene sets involved in mitochondrial respiration and the TCA cycle are enriched among the gain-of-function interaction partners of MEMO1. Based on these findings, we measured the TCA cycle metabolite levels in breast cancer cells with varying levels of MEMO1 expression. Methods: ShRNA knockdown assay was performed to test essentiality of key TCA cycle enzymes. TCA metabolites were quantified using liquid chromatography-tandem mass spectrometry (LC-MS/MS) in MDA-MB-231 (high MEMO1), M67-2 (MEMO1 knockdown), and M67-9 (MEMO1 knockout) cells under iron-depleted, basal iron, and iron-supplemented conditions. Results:ACO2 and OGDH knockdowns inhibit cell proliferation, indicating an essential role of the TCA cycle in MDA-MB-231 metabolism. α-Ketoglutarate and citrate levels exhibited an inverse relationship with MEMO1 expression, increasing significantly in MEMO1 knockout cells regardless of iron availability. In contrast, fumarate, malate, and glutamate levels were elevated in MEMO1 knockout cells specifically under low iron conditions, suggesting an iron-dependent effect. Conclusions: Overall, our results indicate that MEMO1 plays a role in regulating the TCA in cancer cells in an iron-dependent manner.